Emergency planning and response for libraries, archives and museums - Dadson, Emma (Facet, 2012)
Are you prepared? Whether you work with a special collection in a local archive or museum, in a large national library or managing records for a healthcare agency, an emergency plan is critical to your organisation's future. Dadson draws on a decade of experience and award-winning training in this essential practical toolkit, enabling you to respond quickly and effectively to flood, fire and other emergencies.